Portfolio diversification : a pragmatic approach for local investors. - Goh, Seng Kuan. (2013)
As world equity markets liberalize over time, investors are being offered an ever increasing number of investment opportunities. Investors can now choose from a wider selection of stocks from more markets. According to Markorwitz, pioneer of the Portfolio Theory, this enables global investors to increase their overall portfolio returns, or decrease their overall exposure to risks or both, as in most cases. Also, investors can construct and maintain portfolios to better match their risk preferences. For example, risk preferring investors may choose to commit more funds to volatile emerging markets.